2016
DOI: 10.1093/bja/aev436
|View full text |Cite
|
Sign up to set email alerts
|

Simulation as a set-up for technical proficiency: can a virtual warm-up improve live fibre-optic intubation?

Abstract: Virtual warm-up significantly improved performance by residents of FOI in live patients with normal airway anatomy, as measured both by speed and by a scaled evaluation of skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Within the General Surgery literature, both analog 8 and electronic 2,17 simulation techniques have been demonstrated to improve surgical skill in randomized controlled trials. Similar trials have demonstrated effective simulator training in Gynecology, 12 Anesthesiology, 10 and Endovascular Surgery. 11 In the orthopedic literature, much of the early research has focused on arthroscopic procedures.…”
Section: Discussionmentioning
confidence: 72%
“…Within the General Surgery literature, both analog 8 and electronic 2,17 simulation techniques have been demonstrated to improve surgical skill in randomized controlled trials. Similar trials have demonstrated effective simulator training in Gynecology, 12 Anesthesiology, 10 and Endovascular Surgery. 11 In the orthopedic literature, much of the early research has focused on arthroscopic procedures.…”
Section: Discussionmentioning
confidence: 72%
“…In the session in which we observed the effect of a warm-up sample, perceived intensity was significantly lower in the first trial than in subsequent trials. Several studies targeted at athletes (Cervantes & Snyder, 2011;Fradkin, Zazryn, & Smoliga, 2010;Shellock & Prentice, 1985), surgeons (Lee et al, 2012;Samuelson et al, 2016;Weller, 2016), and vocalists (Moorcroft & Kenny, 2012 reported that physical warm-up improves physical performance. Furthermore, other studies reported improvement of cognitive performance following physical warm-up (Elsworthy, Dascombe, & Burke, 2013;Hogan, Mata, & Carstensen, 2013;Pennington & Hanna, 2013) and improvement of cognitive performance following cognitive warm-up (Dinner & Duncan, 1959;Thune, 1951).…”
Section: Improvement Of Perceptual Sensitivity Through Use Of a Warmentioning
confidence: 99%
“…Intentions are more likely to translate into actual actions when they are spelt out in situation‐specific plans . This was supported by a recent trial showing the positive effect of prior virtual practice of specific technical skills for fibreoptic intubation on subsequent success of performing the same procedure on real patients . In comparison, when a critical situation is ‘unpredictable’, planning appears less relevant and cognitive aids are more valuable .…”
Section: Discussionmentioning
confidence: 94%